Organized by Leucò Cultural association Chaired by the Syracuse Council of Culture - Antoniou, Klitsa (My University, 2026)
Kairos: Only the space remembers – Greeks of the East and Greeks of the West Municipality and the Department of Culture of the city of Syracuse Organized by Leucò Cultural association Chaired by the Syracuse Council of Culture Ex-convent of Syracuse ‘’The Place Remember